Effect of Ripasudil on the Change Rates of the Circumpapillary Retinal Nerve Fiber Layer Thickness in Patients With Primary Open-Angle Glaucoma - Katsumasa Sakurai; Kenji Suda; Tadamichi Akagi; Hanako Ohashi Ikeda; Takanori Kameda; Masahiro Miyake; Tomoko Hasegawa; Akitaka Tsujikawa (Journal of Ophthalmology)
Conclusion: The cpRNFLT change rate significantly increased after ripasudil administration, whereas the contribution of the IOP decline was not significant.